Antibodies Against Modified NS1 Wing Domain Peptide Protect Against Dengue Virus Infection - Yen-Chung Lai (Nature Portfolio, 2017)
Abstract Dengue is the most common mosquito-transmitted viral infection for which an improved vaccine is still needed. Although nonstructural protein-1 (NS1) immunization can protect mice against dengue infection, molecular mimicry between NS1 and host proteins makes NS1-based vaccines challenging to develop. Based on the epitope recognized by the anti-NS1 monoclonal Ab (mAb) 33D2 which recognizes a conserved NS1 wing domain (NS1-WD) region but not host proteins, we synthesized a modified NS1-WD peptide to immunize mice. We found that both mAb 33D2 and modified NS1-WD peptide immune sera could induce complement-dependent lysis of dengue-infected but not un-infected cells in vitro. Furthermore, either active immunization with the modified NS1-WD peptide or passive transfer of mAb 33D2 efficiently protected mice against all serotypes of dengue virus infection. More importantly, dengue patients with more antibodies recognized the modified NS1-WD peptide had less severe disease. Thus, the modified NS1-WD peptide is a promising dengue vaccine candidate.